Cultural encounters in the history of East Kalimantan as model for diversity in Indonesia new capital today: studies on Salasilah Negeri Kutai Kerta Negara - Agus Iswanto; Husnul Fahimah Ilyas; Rias Antho Rahmi Suharjo; Muhamad Rosadi; Saeful Bahri; Agus Heryana; Nandang Rusnandar (Cogent Arts & Humanities)
Several ethnic groups in Indonesia have been mentioned in manuscripts from East Kalimantan, an area being developed as the new national capital of Indonesia. One of the manuscripts is Salasilah Negeri Kutai Kerta Negara (SNKKN). The cultural encounters in this text need to be revealed to explore the multicultural facts that were once present in the people’s collective memory. Data were collected by closely reading the text editions. This study found cultural aspects and intercultural relations between ethnicities, namely Javanese, Malay, Chinese, and Bugis, as well as religious elements, beliefs, and traditional knowledge. This interpenetration is motivated by the interests of political legitimacy, religion, friendship, and trading. The study highlights the SNKKN as a model for inclusive cultural encounters, showing that interactions between indigenous communities and diverse groups did not eliminate local traditions. Instead, it reflected core values of openness, respect, and intercultural friendship—among the important principles crucial to the success of a capital city.